Value at risk: proposals on a generalization - Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
The Value at Risk approach (VaR) is more and more used as a tool for risk measurement. The approach however has shortcomings both from a theoretical and a practical point of view. VaR can be classified within existing concepts of risk measurement: it is particularly interpretable as a special measure of shortfall risk. From that point of view VaR will be extended and improved. Eventually return distributions and shortfall measures are calculated for portfolios' including option strategies. Though VaR is held constant across the resulting return distributions quite different valuations of risk arise depending on the shortfall measure used for the comparison.
Keywords: 330; Risiko; Index; Bankrisiko; Theorie